Design and model for the giant magnetostrictive actuator used on an electronic controlled injector. (10th April 2017) - Xue, Guangming; Zhang, Peilin; He, Zhongbo; Li, Ben; Rong, Ce
Abstract: Giant magnetostrictive actuator (GMA) may be a promising candidate actuator to drive an electronic controlled injector as giant magnetostrictive material (GMM) has excellent performances as large output, fast response and high operating stability etc. To meet the driving requirement of the injector, the GMA should produce maximal shortening displacement when energized. An unbiased GMA with a 'T' shaped output rod is designed to reach the target. Furthermore, an open-hold-fall type driving voltage is exerted on the actuator coil to accelerate the response speed of the coil current. The actuator displacement is modeled from establishing the sub-models of coil current, magnetic field within GMM rod, magnetization and magnetostrictive strain sequentially. Two modifications are done to make the model more accurate. Firstly, consider the model fails to compute the transient-state response precisely, a dead-zone and delay links are embedded into the coil current sub-model. Secondly, as the magnetization and magnetostrictive strain sub-models just influence the change rule of the transient-state response the linear magnetostrictive strain-magnetic field sub-model is introduced. From experimental results, the modified model with linear magnetostrictive stain expression can predict the actuator displacement quite effectively.